Insights into adsorption of various gases on extra-framework cations of zeolite: a dispersion corrected DFT study on zeolite cluster models with Li plus , Na plus and K plus ions - Devasia, George; Kumar, Ravi; Vaval, Nayana; Krishnamurty, Sailaja (Microporous and Mesoporous Materials, 2023)
Design of an economical and sustainable gas separation material is relevant in several industrial processes. Zeolites with tunable pore sizes are ideal molecular sieves of many gases. The adsorption centers of these molecular sieves are extra-framework Lewis acid centers. In this study, we attempt to delineate the electronic properties of such centers (Li+, Na+ and K+) and their sorption properties towards N2, O2, CO, CO2 and H2. Negative framework of zeolites are modeled using different cluster models that present distinct electronic environment and role of this environment on the Lewis acidity of the cation. The sorption property towards different gases is evaluated using dispersion corrected DFT studies. The results obtained are benchmarked for one of the studied model using CCSD calculations. The results indicate that while the local environment modulates the adsorption properties, the relative adsorption properties between different ions follow the same order irrespective of the type of negative framework modeled. This reveals that intrinsic atomic properties of the charge compensating cations drive the sorption properties of the zeolites. Adsorption energies compounded with the analysis of IR stretching frequencies of the adsorbed gases reveals that Li centers shows molecular adsorption (charge donation to the cationic centers) towards N2 as compared to O2 and towards CO2/CO as compared to H2, demonstrating the applicability of Li-Zeolites as ideal membranes for oxygen concentrators and syngas separation. These adsorption studies are ratified by the BOMD simulations at 300 K, where H2 and O2 desorbs while N2, CO and CO2 remains adsorbed to the cationic site.
Keywords: BOMD simulation; CO/CO2/H2 separation; Extra-framework cation; N2/O2 separation; zeolites

Scalable approach using a gC3N4 -covalent organic framework hybrid catalyst towards sustainable hydrogen production from seawater and wastewater - Asokan, Kiran; Bhagyasree, T. M.; Devasia, George; Krishnamurty, Sailaja; Solim, Sabah; Rueda, Lina; Al-Mohannadi, Dhabia M.; Al-Hashimi, Mohammed; Kakosimos, Konstantinos; Santhosh Babu, Sukumaran (CHEMICAL SCIENCE, 2024)

Binderless low silica X zeolite for methane separation from binary CO2/CH4 biogas stream: A comprehensive experimental and computational study - Yadav, Tushar R.; Shrotri, Aadesh R.; Kate, Pranjali N.; Devasia, George; Niphadkar, Prashant S.; Mali, Nilesh A.; Krishnamurty, Sailaja; Bokade, Vijay V.; Nandanwar, Sachin U. (Journal of Industrial and Engineering Chemistry, 2025)
This study presents the synthesis of binderless Na-LSX (B-Na-LSX) and binderless NaK-LSX (B-NaK-LSX). XRD, SEM, EDS, and N-2 physisorption were used for characterization of samples. Computational modelling of prepared sorbent was performed for the fundamental understanding of zeolite topology and adsorption behaviour. The breakthrough experiments are used to evaluate the adsorption capacities on CO2/CH4 (40/60 vol%) binary biogas stream. The results were compared with commercial Na-LSX (C-Na-LSX). The breakthrough adsorption capacity of B-Na-LSX was 3.08 mmol g(-1) and 0.29 mmol g(-1) of CO2 and CH4, respectively, at 300 K and 1 bar. CO2 sorption capacity of B-Na-LSX was similar to 11 % and similar to 17 % higher than B-NaK-LSX (2.77 mmol g(-1)) and C-Na-LSX (2.56 mmol g(-1)), respectively. DFT study reveals that the higher adsorption of CO2 over CH4 was attributed to higher charge transfer from CO2 to zeolite framework. Dual-bed six-step Pressure Swing Adsorption (PSA) was performed on B-Na-LSX at 6 bar. similar to 232 cycles were run with above 98 % of CH4 purity and similar to 74 % of recovery. The life-cycle test of sorbent was studied. It was implied that the designed sorbent is effective to produce the high purity of CH4 and can be utilized for a longer period for CH4 production.
Keywords: Binderless; Biogas; LSX zeolite; methane; PSA; Separation

Diamondoid all-carbon porous aromatic framework host for lithium-sulfur batteries - Kumar, Viksit; Javaregowda, Bharathkumar H.; Devasia, George; Narayanan, Aswini; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Small, 2025)
Lithium-sulfur batteries (LSBs) hold incredible potential as next-generation energy storage systems. However, practical applications of LSBs are significantly hindered by several critical challenges. For the first time, scalable all-carbon porous 3D polymers (3DPs) that do not contain heteroatoms or functional groups and do not require post-functionalization are investigated as hosts in lithium-sulfur batteries, demonstrating enhanced cycling stability and overall battery performance. The pyrene-containing 3DP exhibits 75% capacity retention after 600 cycles at 1 C and 52% capacity retention after 1300 cycles at 0.2 C, better than phenyl comprising 3DP. Furthermore, even at higher sulfur loading (4.1 mg cm(-2)) with an electrolyte/sulfur ratio of 5 mu L mg(-1), pyrene 3DP displayed a high capacity of 600 mA h g(-1) and stable performance over 250 cycles with negligible capacity fade. The defined pore structure of 3DPs prevents the migration of polysulfides through physical confinement and the large pi -clouds of 3DPs interact with the negative charge-bearing polysulfides generated in charge-discharge cycles through anion-pi interaction. In this way, The design ensures that the host 3DPs interact with neutral sulfur and anionic polysulfides, resulting in an excellent performance.
Keywords: 3D polymers; Batteries; Li-Sulfur battery; porous materials; pyrene

Evaluating the preferential adsorption of N2 from a binary mixture of N2/O2 on extra-framework cations of zeolites: a computational and experimental study - Devasia, George; Nandanwar, Sachin U.; Krishnamurty, Sailaja (Physical Chemistry Chemical Physics, 2025)
Separation of N2 from a N2/O2 gas mixture is critical for various industrial/medical applications. Temperature/pressure swing adsorption is the top-notch industrial technology used for this separation, where zeolites are the materials used for adsorption. Zeolite X/Y with Li+ as an extra-framework cation is the best-known sorbent for N2 gas molecules. However, the present net zero emission scenario has made lithium a critical element, making it imperative to implement its alternative in various other technologies. In this context, the present work is a computational evaluation to identify a cation that can replace Li+ for preferential adsorption of N2 over O2. The DFT study, based on parameters such as selective adsorption energies of N2 over O2 and IR stretching frequencies of the adsorbed N2 and O2 molecules, identifies Mg2+, Ca2+, Sr2+, Co2+ and Zn2+ as potential cations. These cations have preferential adsorption for N2 over O2 by 10 kJ mol-1 or more. However, BOMD simulations reveal that only Mg2+, Ca2+, Co2+ and Zn2+ keep the N2 molecule bound at 300 K and the O2 molecule gets desorbed from these frameworks. The desorption temperature of N2 on Ca2+ and Zn2+ is 350 K and on Mg2+ is 400 K. These observations are corroborated by electronic charges on cations and molecular orbitals. Significantly, Ca2+ is identified to adsorb up to 2 N2 molecules, making it an ideal candidate for N2/O2 separation in place of Li+. To validate this, we have carried out an experimental study that showed a good N2 adsorption capacity of 2.1 mmol g-1 for Ca2+.

Long cycling stability imparted to li-ion batteries by conjugated polymers with low dihedral angles and high electron density on functional groups - Kargude, Radhakisan; Srinivasalu, Hari Haran; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam (ACS Applied Polymer Materials, 2025)
In conjugated polymers, dihedral angles at bonds connecting their monomers impact the polymers' properties such as the packing of the polymer chains, bandgap, and conductivity. These properties are expected to impact the performance of rechargeable Li-ion batteries because the Li-ion transport and conductivity of the polymers are two important parameters. To understand this, we designed and synthesized two polymers with two different dihedral angles. The polymer, Poly(EDOT-DPP), comprising diketopyrrolopyrrole (DPP) and ethylenedioxythiophene (EDOT) as monomers, showed a low dihedral angle of 2 degrees. On the other hand, the polymer, Poly(EDOT-i-Ind), comprising EDOT and i-Indigo (i-Ind) showed a dihedral angle of 17 degrees. Density functional theory (DFT) studies showed that the electron density at the carbonyl moiety of EDOT-DPP is higher than that of EDOT-i-Ind. This resulted in a higher Li+ binding energy of -3.665 eV for EDOT-DPP and a lower Li+ binding energy of -3.464 eV for EDOT-i-Ind. Battery electrodes were fabricated using either Poly(EDOT-DPP) or Poly(EDOT-i-Ind) with multiwalled carbon nanotubes as conducting fillers in the absence of any binders. The Li+ ion diffusion coefficient ( D Li + ) measured for the as prepared batteries based on Poly(EDOT-DPP) was found to be 3.9 x 10-19 cm2/s, which is slightly higher than that found for Poly(EDOT-i-Ind). However, after 2000 cycles, the D Li + increased by about two orders of magnitude for both polymers. Due to the low dihedral angle in the case of Poly(EDOT-DPP), the D Li + was found to be 21% higher than that of Poly(EDOT-i-Ind). The higher binding of Li+ ions with Poly(EDOT-DPP) and Li+ ion diffusion improved the specific capacity and cycling performance of batteries fabricated with this polymer. At a current density of 0.2 A/g, Poly(EDOT-DPP) showed a 39% higher specific capacity than the Poly(EDOT-i-Ind) polymer after 2000 cycles. The batteries also showed stable performance over 2000 cycles with an insignificant decrease in specific capacity.
Keywords: dihedral angle; diketopyrrolopyrrole; i-indigo; Li-ion battery; Li-ion transport

Architecting nanographenes for efficient energy storage by tailoring molecular conformation and packing - Kumar, Viksit; Javaregowda, Bharathkumar H.; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Santhosh Babu, Sukumaran (Journal of Materials Chemistry A, 2026)
Structural tuning of electrode materials to enhance electron transport, ion storage capacity, and Li+ diffusion is crucial for developing high-performance lithium-ion batteries (LIBs). In this context, organic functional materials are attractive candidates. Herein, we report a unique molecular design of regioisomeric nanographenes (NGs) with distinct geometries, packing, and topologies for lithium storage as LIB anodes. The nonplanar architectures suppress layer restacking compared to planar analogues, leading to improved electrochemical performance. The pi-extended helical NG 36NG, with larger interlayer spacing and a unique helical geometry, enables faster Li+ diffusion and delivers a higher specific capacity of 719.93 and 203.01 mAh g-1 at 0.1 and 1 A g-1, respectively, with stable performance over 6000 cycles, outperforming 27NG (525.46 and 113.17 mAh g-1 at 0.1 and 1 A g-1, respectively). Single-crystal X-ray analysis reveals markedly different molecular arrangements, directly correlating topology and packing with Li+ storage. This work highlights the critical role of molecular topology in LIB anodes and motivates the design of tailored pi-extended helical nanographenes for energy-storage applications.

Orthogonally Engineered Redox-Active Polyimide-Carbon Nanotube Hybrids for Long-Life Lithium-Ion Battery Cathode - Thanasekar, Chandragopal; Javaregowda, Bharathkumar H.; Veer, Sairam Dnyaneshwar; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Small, 2026)
The diverse structural tunability and engineered electronic properties of organic polymers have sparked significant interest in their use as cathode materials for lithium-ion storage. Recent advances suggest that organic cathodes can serve as promising alternatives to conventional metal oxide counterparts due to their elemental abundance, safety, and high theoretical capacity. However, developing cathode materials that simultaneously exhibit high specific capacity, long cycle life, and excellent rate performance remains a critical challenge. In this study, the synthesis and application of a redox-active polyimide based on orthogonally positioned, active site-rich mellitic trianhydride (MTA) and naphthalene diimide (NDI), integrated with multi-walled carbon nanotubes (MWCNTs), referred to as MTA-NDI@CNT are reported. The pristine MTA-NDI polymer demonstrates a specific capacity of 60 mAh g-1 at a current density of 200 mA g-1 and exhibits remarkable cycling stability over 20 000 cycles. Upon hybridisation with CNT (10 wt.%), the composite (MTA-NDI@CNT) delivers a nearly threefold enhancement in specific capacity, reaching 170 mAh g-1 at 500 mA g-1, along with stable cycling performance over 1300 cycles and 60.5% capacity retention.
Keywords: cathode; CNT; lithium-ion battery; orthogonality; Polyimide